PEGylated Chitosan Nanoparticles Encapsulating Ascorbic Acid and Oxaliplatin Exhibit Dramatic Apoptotic Effects against Breast Cancer Cells - Sherif Ashraf Fahmy; Asmaa Ramzy; Asmaa A. Mandour; Soad Nasr; Anwar Abdelnaser; Udo Bakowsky; Hassan Mohamed El-Said Azzazy (MDPI AG, 2022)
This study aims to design a pH-responsive dual-loaded nanosystem based on PEGylated chitosan nanoparticles loaded with ascorbic acid (AA) and oxaliplatin (OX) for the effective treatment of breast cancer. In this regard, non-PEGylated and PEGylated chitosan nanoparticles (CS NPs) loaded with either ascorbic acid (AA), oxaliplatin (OX), or dual-loaded with AA-OX were fabricated using the ionotropic gelation method. The hydrodynamic diameters of the fabricated AA/CS NPs, OX/CS NPs, and AA-OX/CS NPs were 157.20 ± 2.40, 188.10 ± 9.70, and 261.10 ± 9.19 nm, respectively. While the hydrodynamic diameters of the designed AA/PEG-CS NPs, OX/PEG-CS NPs, and AA-OX/PEG-CS NPs were 152.20 ± 2.40, 156.60 ± 4.82, and 176.00 ± 4.21 nm, respectively. The ζ-potential of the prepared nanoparticles demonstrated high positive surface charges of +22.02 ± 1.50, +22.58 ± 1.85 and +40.4 ± 2.71 mV for AA/CS NPs, OX/CS NPs, and AA-OX/CS NPs, respectively. The ζ-potential of the PEGylated CS NPs was reduced owing to the shielding of the positive charges by the PEG chains. Additionally, all the prepared nanoparticles exhibited high entrapment efficiencies (EE%) and spherical-shaped morphology. The chemical features of the prepared nanoparticles were investigated using Fourier transform infrared (FTIR) spectroscopy. Release studies showed the capability of the prepared non-PEGylated and PEGylated chitosan NPs to release their cargo in the acidic environment of cancer tissue (pH 5.5). Furthermore, the AA/CS NPs, AA/PEG-CS NPs, OX/CS NPs, OX/PEG-CS NPs, AA-OX/CS NPs and AA-OX/PEG-CS NPs exhibited remarkable cytotoxic activities against breast adenocarcinoma (MCF-7) cells with IC50 values of 44.87 ± 11.49, 23.3 ± 3.73, 23.88 ± 6.29, 17.98 ± 3.99, 18.69 ± 2.22, and 7.5 ± 0.69 µg/mL, respectively; as compared to free AA and OX (IC50 of 150.80 ± 26.50 and 147.70 ± 63.91 µg/mL, respectively). Additionally, treatment of MCF-7 cells with IC50 concentrations of AA, AA/CS NPs, AA/PEG-CS NPs, OX, OX/CS NPs, OX/PEG-CS NPs, AA-OX/CS NPs or AA-OX/PEG-CS NPs increased the percentages of early apoptotic cells to 5.28%, 9.53%, 11.20%, 5.27%, 13.80%, 8.43%, 2.32%, and 10.10%, respectively, and increased the percentages of late apoptotic cells to 0.98%, 0.37%, 2.41%, 2.06%, 0.97%, 9.66%, 56%, and 81.50%, respectively. These results clearly indicate that PEGylation enhances the apoptotic effect of AA and OX alone, in addition to potentiating the apoptotic effect of AA and OX when combined on MCF-7 cells. In conclusion, PEGylated chitosan nanoparticles encapsulating AA, OX, or AA and OX represent an effective formula for induction of apoptosis in MCF-7 cells.